Labour market forecasts and their use: Practices in the Scandinavian countries - Magnus Lindskog (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
The ongoing restructuring of today's labour markets and the swift changes in occupational structures and skill requirements generate a risk for unbalanced growth in the supply and demand for qualifications. This paper concentrates on the instruments employed in Scandinavia to identify labour market mismatches, understood as shortages of qualifications related to a certain occupation or education group. There are various actors engaged in the forecasting of labour market developments in the individual countries. The public employment services (PES) stand out as the main actor concerning the identification of short-term needs and the characteristics of current mismatches. The PES efforts are primarily carried out on the regional and/or local levels, and the central tools are comprehensive company surveys and ongoing regular contacts with the surrounding society. The information obtained is essential to adjust the focus of labour market training, which has the primary objective to support the employment offices in their efforts to smooth the matching process on the labour market. – – Die kontinuierlichen Strukturveränderungen an den Arbeitsmärkten führen zu starken Veränderungen in der Beschäftigungsstruktur und den Qualifikationserfordernissen. Unter diesen Bedingungen besteht die Gefahr für Ungleichgewicht im Angebot und in der Nachfrage von Qualifikationen. Das vorliegende Papier fokussiert auf die Instrumente, die in Skandinavien eingesetzt werden, um Mismatch - verstanden als nicht erfüllte Qualifikationserfordernisse, die an eine bestimmte Tätigkeit oder ein bestimmtes Qualifikationsniveau gerichtet sind - zu identifizieren. Es gibt verschiedene Akteure, die an Arbeitsmarktprognosen in den einzelnen skandinavischen Ländern arbeiten. Bezogen auf kurzfristige Prognosen sind die nationalen Arbeitsmarktverwaltungen (PES) mit Abstand die wichtigsten. Die zentralen Werkzeuge der PES sind umfassende statistische Untersuchungen und kontinuierliche Kontakte mit der umgebenden Gesellschaft, die hauptsächlich auf der regionalen und/oder lokalen Ebene durchgeführt werden. Die Prognosen, die auf die Unterstützung der Tätigkeit der Arbeitsämter ausgerichtet sind, beeinflussen den Fokus der beruflichen Aus- und Weiterbildung.
Keywords: 330; Arbeitsmarktprognose; Berufsbedarf; Qualifikation; Strukturelle Arbeitslosigkeit; Dänemark; Norwegen; Schweden